2013
DOI: 10.1039/c3an36866a
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and synthesis of SERS labels

Abstract: SERS labels are a new class of nanotags for optical detection based on Raman scattering. Central advantages include their spectral multiplexing capacity due to the small line width of vibrational Raman bands, quantification based on spectral intensities, high photostability, minimization of autofluorescence from biological specimens via red to near-infrared (NIR) excitation, and the need for only a single laser excitation line. Current concepts for the rational design and synthesis of SERS labels are summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
147
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 129 publications
0
147
0
1
Order By: Relevance
“…123,236 PEG is a biocompatible polymer able to prevent nonspecific adsorption of proteins and other cellular components, leading to prolonged blood circulation lifetimes in vivo. 14,237,238 The great ability of PEG to prevent the biofouling of particles is attributed to a combination of flexibility and strong interaction with water molecules where protein adsorption would lead to an unfavorable increase in free energy. 239 PEG ligands can be anchored to noble metal surfaces through a distal thiol functional group.…”
Section: Sers Nanoparticle Tagsmentioning
confidence: 99%
“…123,236 PEG is a biocompatible polymer able to prevent nonspecific adsorption of proteins and other cellular components, leading to prolonged blood circulation lifetimes in vivo. 14,237,238 The great ability of PEG to prevent the biofouling of particles is attributed to a combination of flexibility and strong interaction with water molecules where protein adsorption would lead to an unfavorable increase in free energy. 239 PEG ligands can be anchored to noble metal surfaces through a distal thiol functional group.…”
Section: Sers Nanoparticle Tagsmentioning
confidence: 99%
“…SERS nanotags, as an alternative label, provide unique optical properties and potential for simultaneous and multiple detection due to the advantages of SERS nanotags over the fluorescent labels including the multiplexing capability for simultaneous target detection, quantification using the SERS fingerprint and the need for only a single laser excitation wavelength, and high photostability [21,22]. Typically, SERS nanotags (as shown in Fig.…”
Section: Sers Nanotagsmentioning
confidence: 99%
“…1a), (ii) a few atoms and/or high symmetry, resulting in a minimal number of Raman bands for multiplexing (Fig. 1b), (iii) low or no photobleaching for the stability of signal, and (iv) surface groups for binding the metal colloid surface with target molecules [22]. As an typical example, Graham et al reported the use of either custom-built benzotriazoles [67] or commercially available dyes (BODIPY, Cy5.5, etc.)…”
Section: Sers Nanotagsmentioning
confidence: 99%
See 1 more Smart Citation
“…[213][214][215] With its narrow and distinct spectral peaks, SERS could potentially be better suited than standard fluorescent-based methods for highly multiplexed applications. [216][217][218] Indeed, SERS particles labelled with various Raman reporters have enabled various multiplex detection applications 219 especially in clinical applications. 220,221 However, to the best of our knowledge, SERS has not been applied to any multiplex RPA applications in agriculture.…”
Section: Introductionmentioning
confidence: 99%